IMPACT OF MICROFINANCE INSTITUTIONS ON FINANCIAL LITERACY IN NORTH CENTRAL GEO-POLITICAL ZONE NIGERIA - Ajibola, Ibrahim Majeed; Saheed, Daud Omotosho; Adedoyin, Lukman (Copernican Journal of Finance & Accounting, 2021)
Inclusive financial literacy through Microfinance Institutions activities is becoming a policy issue in both developed and developing nations of the world as it has been perceived as a veritable tool for economic development. This work examines the impact of Microfinance Institutions on financial Literacy in North Central Geo-Political Zone Nigeria. The specific objectives are to establish the relationship between saving mobilization as microfinance institutions operations and financial literacy, analyze the effect of microfinance institutions accessibility on E-banking platform usage and identify the effects of microfinance institutions activities on the financial decisions of the rural dwellers. Descriptive design method was adopted; 50 respondents was selected from each of the six Microfinance Institutions that was selected from each of the six states of the north central geo-political zone that serve as the fair representation of the population under study a total of 1800 questionnaires were administered out of which 1494 was returned. Data for the study were collected primarily through questionnaire from the 1494 respondents that serve as the fair representations for the population under study. The formulated hypotheses were tested with the aid of regression and correlation while preliminary test was done with the aid of Kolmogorov-Smirnov and Shapiro Wilk with a view to ascertain the normality of the data. Similarly, Reliability test was conducted with the aid of Cronbach’s Alpha. The overall results of the regression analysis reveals that a positive relationship exist between MFIs activities and financial literacy given cognizance to the reported coefficients on the adopted variables. Therefore, it was recommended that Government should promote financial sector deepening by licensing more microfinance institutions, to promote accessibility to finance among its populous to improve the level of financial literacy in Nigeria. This will increase their ability to save and borrow thereby contribute positively to economic development.